The male ejaculate as inhibitor of female remating in two tephritid flies - Abraham, Solana (2016)
The inhibition of female receptivity after copulation is usually related to the quality of the first mating. Males are able to modulate female receptivity through various mechanisms. Among these is the transfer of the ejaculate composed mainly by sperm and accessory gland proteins (AGPs). Here we used the South American fruit fly Anastrepha fraterculus (where AGP injections inhibit female receptivity) and the Mexican fruit fly Anastrepha ludens (where injection of AGPs failed to inhibit receptivity) as study organisms to test which mechanisms are used by males to prevent remating. In both species, neither the act of copulation without ejaculate transfer nor sperm stored inhibited female receptivity. Moreover, using multiply mated sterile and wild males in Mex flies we showed that the number of sperm stored by females varied according to male fertility status and number of previous matings, while female remating did not. We suggest female receptivity in both flies is inhibited by the mechanical and/or physiological effect of the full ejaculate. This finding brings us closer to understanding the mechanisms through which female receptivity can be modulated.